Design and Implementation of an IoT-Based Dust Exposure Monitoring System for Marble Cutting Activities in Campus Environment - Rudi Arif Candra; Depi Ginting; Dirja Nur Ilham; Arie Budiansyah; Erwinsyah Sipahutar (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2026)
Marble cutting activities in campus workshop environments generate substantial concentrations of airborne particulate matter, particularly PM2.5 and PM10, which pose serious risks to occupational health and ambient air quality. This study presents the design, implementation, and experimental evaluation of a real-time IoT-based dust exposure monitoring system with emphasis on sensing performance, data reliability, and environmental analysis. The system employs a laser scattering dust sensor (PMS7003) integrated with an ESP8266 microcontroller for data acquisition and edge preprocessing, and utilizes Wi-Fi communication with the MQTT protocol for low-latency data transmission to a cloud-based monitoring platform. Sensor calibration was conducted using linear regression against a reference air quality monitor, resulting in improved measurement accuracy with a coefficient of determination (R²) of 0.96 for PM2.5 and 0.94 for PM10. The system operates with a 5-second sampling interval and applies a moving average filter (window size = 5) to reduce signal noise. Experimental deployment was carried out in a campus marble workshop over a 5-day observation period. Results indicate that during active cutting sessions, PM2.5 concentrations ranged from 85 to 210 µg/m³ and PM10 from 120 to 350 µg/m³, significantly exceeding WHO air quality guidelines (PM2.5: 15 µg/m³, PM10: 45 µg/m³, 24-hour mean). Peak concentrations were observed within the first 10 minutes of operation, followed by gradual dispersion depending on ventilation conditions. Network performance evaluation shows an average transmission latency of 1.8 seconds, packet delivery ratio of 97.2%, and system uptime of 99% over the testing period. Power consumption analysis indicates an average current draw of 82 mA, enabling efficient long-term deployment. The results confirm that the proposed system provides accurate, stable, and high-resolution monitoring of particulate pollution, supporting real-time decision-making for exposure mitigation and smart environmental management in campus settings.